ANALISIS PENGARUH ON STREET PARKING TERHADAP KINERJA LALU LINTAS PADA JALAN PEKIRINGAN, KOTA CIREBON, JAWA BARAT - Farhan, Ohan; Hariani, Mira Lestira; Lumtunnanie, Annisa (Politeknik Negeri Semarang, 2023)
Management of on-street parking needs to be considered because it affects to traffic performance. This study aims to analyze the effect of on street parking to traffic performance on Jalan Pekiringan, Cirebon City. Data collection methods used in this study are primary data and secondary data. Primary data obtained through direct survey include: geometric data, vehicles volume data and parking volume data. While secondary data was obtained through Google Earth and related institution which included Geometric data for Cirebon City Roads. The analytical method used in this research is the analysis of the road segment capacity referring to the 1997 Indonesian Road Capacity Manual (MKJI 1997). Based on the result, the degree of saturation reaches 0.31 in conditions with on-street parking at this time and the degree of saturation in the future will reach 0.38 and 0.55 (level D) if parking on the street is allowed. The results of the degree of saturation with off street parking are 0.25 at Peak Hour.